Survival and inactivation of classical swine fever virus isolated from pigs of Asom, India - RAJBONGSHI, GITIKA; BARMAN, N N; DAS, S K (The Indian Journal of Animal Sciences, 2011)
The present study was undertaken to evaluate stability and inactivation of the local isolates of classical swine fever virus (CSFV) along with the standard lapinized cell culture adapted CSF virus vaccine exposing to various physical and chemical agents. Vaccine strain and local isolates of CSFV adapted in PK-15 cell line were exposed to different temperatures (4, 27, 60°C), pH (2, 7, 14) and chemicals (2% NaOH, 20% chloroform, 0.5% trypsin) at various time periods. TCID50 of the virus residue was estimated at the end of each treatment. Results showed that all the CSFV isolates lost their virus titre completely within 10 min at 60°C, at pH 2 and pH 14 within 30 min. Viruses exposed to 20% chloroform, 0.5% trypsin and 2% sodium hydroxide, inactivated completely within 60 min. On the other hand, at 27°C, within 60–120 min virus titre was reduced by 0.5–1.0 log10 and at 4°C, titre of the isolates were reduced by 0.5–1.0 log10 within 15–30 days. Exposure to different pH levels showed that CSFV titre remained stable at pH 7 within 15 to 30 min at room temperature. The work provides basic information on physico-chemical properties of cell culture adapted Indian isolates of CSF virus and also a comparison with lapinized CSFV.